Women’s Political Participation - Video showing Team of Researchers with a Woman Politician in an Interview in Ibadan - Ademola-Adeoye, Feyisayo (Locating the Albatross in Women's Political Participation in Sub-Saharan Africa, 2021)
Video on pilot study recorded in Ibadan, Oyo State
Keywords: Women; Sub-Saharan Africa; Political rights; Political participation; Structural Barriers; Political Barriers; Politics